Pengaruh Environmental Social Governance (ESG), Good Corporate Governance (GCG) dan Kebijakan Dividen terhadap Kinerja Keuangan Perusahaan - Novriani, Amelia Safitri; Sudiyatmoko, Agus (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG), Good Corporate Governance (GCG), and dividend policy on the financial performance of companies listed on the LQ45 index. The motivation arises from the fluctuating performance of LQ45 companies during 2019-2023, which highlights the need to evaluate factors influencing financial sustainability. Using a quantitative approach, this research analyzes secondary data from financial statements, annual reports, and sustainability reports. A purposive sampling method was applied, resulting in 16 companies selected from the population of 45 LQ45 firms. Panel data regression with the Random Effect Model (REM) was employed using EViews 12. The findings reveal that ESG and GCG have a positive and significant effect on financial performance, while dividend policy shows no significant influence. Simultaneously, the three variables significantly affect performance, with an adjusted R² of 17%. These results underscore the importance of sustainability practices and strong governance in enhancing company performance and investor confidence, while dividend policy is not a decisive factor. This study contributes to the literature by providing evidence from emerging capital markets and offers managerial implications for strengthening competitiveness through ESG and GCG practices.